ARAHAN KEBIJAKAN MITIGASI PADA ZONA RAWAN BANJIR KABUPATEN LIMAPULUH KOTA, PROVINSI SUMATERA BARAT - Iswandi Umar; Indang Dewata (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Indonesia is a country that has a wet tropical climate, so that about 60 % of the cities in Indonesia is very a hazard to flood. The floods have caused many losses to humans. The purpose of this study is determine the direction of development policy mitigation of flood hazard zones in Limapuluh Kota District, by using GIS analysis with the overlay technique. The indicators used to determine the flood hazard zones are rainfall, slope, landform, soil type, geology, elevation, and land use. Mitigation policy directives using AHP analysis involving 15 experts with conservation criteria, regulations, community capacity. The results showed 6,2 % is a very flood zone. Three main landing to reduce the impact of floods is disaster education, improved socialization in flood hazard zones, and planning of based spatial disaster.